A MESSAGE FAILURE ANALYSIS OF SYSTEMS EXECUTING AVERAGE CONSENSUS ALGORITHM - Martin Kenyeres; Jozef Kenyeres; Vladislav Skorpil (European Scientific Journal, ESJ, 2015)
A communication failure is an aspect which may affect a whole system so significantly that it is unable to provide its functionality any longer. In this paper, we have implemented average consensus algorithm into 30 distributed systems and focused on examining the effect of a message delivery failure modeled by Bernoulli distribution. We modified the probability of a failure occurrence and examined the effect of these changes on the number of the iterations necessary for a distributed system to achieve the consensus and the deviation of the final values from the expected ones.